Real business cycles with a human capital investment sector and endogenous growth: Persistence, volatility and labor puzzles - Jing Dang; Max Gillman; Michal Kejak (Cardiff University, Cardiff Business School, 2011)
A positive joint two-sector productivity shock causes Rybczynski (1955) and Stolper and Samuelson (1941) effects that release leisure time and initially raises the relative price of human capital investment so as to favor it over goods production. This enables a basic RBC model, modified by having the household sector produce human capital investment sector, to succeed along related major dimensions of output, consumption, investment and labor, similar to the international approach of Maodifying the dynamics relative to the important work of Jones et al. (2005), two key US facts stressed by Cogley and Nason (1995) are captured: persistent movements in the growth rates of output and hump-shaped impulse responses of output. Further, physical capital investment has data consistent persistence within a hump-shaped impulse response. And Gali's (1999) challenging empirical finding that labour supply decreases upon impact of a positive productivity shock is reproduced, while volatility in working hours is also data-consistent because of the substitution between market and nonmarket sectors.
Keywords: E24; E32; O41; 330; real business cycle; human capital; persistence; volatility; labor; Produktivität; Schock; Qualifikation; Arbeitsangebot; Arbeitszeit; Theorie